Exploring the molecular basis of efficient feed utilization in low residual feed intake slow-growing ducks based on breast muscle transcriptome - Lei Wu; Zhong Zhuang; Wenqian Jia; Yongpeng Li; Yijia Lu; Minghong Xu; Hao Bai; Zhixiu Wang; Guobin Chang; Yong Jiang (Poultry Science)
Residual feed intake (RFI) has recently gained attention as a key indicator of feed efficiency in poultry. In this study, 800 slow-growing ducks with similar initial body weights were reared in an experimental facility until they were culled at 42 d of age. Thirty high RFI (HRFI) and 30 low RFI (LRFI) birds were selected to evaluate their growth performance, carcass characteristics, and muscle development. Transcriptome and weighted gene co-expression correlation network analyses of pectoral muscles were conducted on six LRFI and six HRFI ducks. The results revealed that selecting for LRFI significantly reduced feed consumption (P < 0.05) and improved feed efficiency without affecting the growth performance, slaughter rate, or meat quality of ducks (P > 0.05). Moreover, compared with HRFI ducks, LRFI ducks had a lower pectoral muscle fat content (P < 0.05), larger muscle fiber diameter and area (P < 0.05), and lower muscle fiber density (P < 0.05). There were significant differences in gene expression between LRFI and HRFI ducks, with 102 upregulated and 258 downregulated genes, which were enriched in the PPAR signaling pathway, adipocytokine signaling pathway, actin cytoskeleton regulation, ECM-receptor interaction, and focal adhesion. The expression of genes associated with fat and energy metabolism, including ACSL6, PCK1, APOC3, HMGCS2, PRKAG3, and G6PC1, was downregulated in LRFI ducks, and weighted gene co-expression correlation network analysis identified PRKAG3 as a hub gene. Our findings indicate that reduced mitochondrial energy metabolism may contribute to the RFI of slow-growing ducks, with PRKAG3 playing a pivotal role in this biological process. These findings provide novel insights into the molecular changes underlying RFI variation in slow-growing ducks.